Monetary and Banking History : Essays in Honour of Forrest Capie. - Wood, Geoffrey (Taylor & Francis, 2011)
Forrest Capie is an eminent economic historian who has published extensively on a wide range of topics, with an emphasis on banking and monetary history, particularly in the nineteenth and twentieth centuries, but also in other areas such as tariffs and the interwar economy. He is a former editor of the Economic History Review, one of the leading academic journals in this discipline. Under the steely editorship of Geoffrey Wood, this book brings together a stellar line of of contributors - including Charles Goodhart, Harold James, Michael Bordo, Barry Eichengreen, Charles Calomiris, and Anna S.